Optimal battery and fuel cell operation for energy management strategy in MG - Jabir, Muhammad; Mokhlis, Hazlie; Muhammad, Munir Azam; Illias, Hazlee Azil (Institution of Engineering and Technology, 2019)
Microgrid (MG) with optimal operating (OC) and capital cost (CC) is highly required. This study presents dual-mode energy management system (DM-EMS) operation with the objective of minimising the overall OC of the MG. DM-EMS determines the best mode to operate battery and fuel cell at a particular time and its duration to operate MG with minimum cost. The CC of an MG is mainly depending on battery size and battery life. In this study, novel battery sizing method by using the proposed life cycle cost (LCC) function is introduced. Considering the impact of battery size and life in the OC and CC of an MG, the proposed DM energy management strategy and novel battery sizing are concurrently optimised by using the proposed LCC function. The proposed strategy is validated using an MG system consisting of wind, battery storage and fuel cell. The results show that better optimal OC and CC with an accurate optimal battery capacity of an MG are achieved. In addition, analysis on the optimal battery size variations for different battery level [state of charges (SOCs)] is conducted. Changes in OCs and CC for the different range of initial battery SOC are also assessed. © The Institution of Engineering and Technology 2019.